2016
DOI: 10.3329/bjmm.v1i2.21507
|View full text |Cite
|
Sign up to set email alerts
|

LD Bodies From Blood Buffy Coat: an Easy Approach for Definitive Diagnosis of Visceral Leishmaniasis

Abstract: This observational study was carried out as a preliminary one to see the effectiveness and reliability of an easy noninvasive approach for the confirmatory diagnosis of Visceral Leishmaniasis (VL) by detection of amastigote forms (LD bodies) of the parasite. Clinically suspected 73 febrile cases were investigated by examination of bone marrow/splenic aspirate to detect LD bodies, of whom 57 (41.61%) showed LD positive result on microscopy and/or culture in modified Novy, Nichole, MacNeal (NNN) medium. Blood bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Diagnosis of VL, mainly by splenic/bone marrow aspiration is considered as gold standard. Splenic aspiration is more sensitive (85-90%) as compared to bone marrow aspiration (50-60%) 16 . However, these days PCR/rt-PCR with splenic aspiration can be more sensitive and specific.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of VL, mainly by splenic/bone marrow aspiration is considered as gold standard. Splenic aspiration is more sensitive (85-90%) as compared to bone marrow aspiration (50-60%) 16 . However, these days PCR/rt-PCR with splenic aspiration can be more sensitive and specific.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of buffy smear was found to be 37.8% which is in consistent with results reached by Diro et al (2017) who reported a sensitivity of 19.5% and Rohrs (1964) a sensitivity of 35%. Shamsuzzaman et al (2007) used the method of density gradient centrifugation using mono-nuclear cell separation fluid "Lymphoprep"and the sensitivity raised to 92.98%. This low percentage could be attributed to the method used for the collection of the buffy coat layer from the blood.…”
Section: Resultsmentioning
confidence: 99%